Techno-Functional, Nutritional and Environmental Performance of Protein Isolates from Blue Lupin and White Lupin - Martin Vogelsang-O’Dwyer; Juergen Bez; Iben Lykke Petersen; Marcel Skejovic Joehnke; Andreas Detzel; Mirjam Busch; Martina Krueger; Lilit Ispiryan; James A. O’Mahony; Elke K. Arendt; Emanuele Zannini (Foods, 2020)
Similarly prepared protein isolates from blue lupin (Lupinus angustifolius) and white lupin (L. albus) were assessed in relation to their composition, functional properties, nutritional attributes and environmental impacts. Blue lupin protein isolate (BLPI) and white lupin protein isolate (WLPI) were found to be quite similar in composition, although differences in the electrophoretic protein profiles were apparent. Both lupin protein isolates (LPIs) had good protein solubility (76.9% for BLPI and 69.8% for WLPI at pH 7) and foaming properties. However, a remarkable difference in heat gelation performance was observed between BLPI and WLPI. WLPI had a minimum gelling concentration of 7% protein, whereas BLPI required 23% protein in order to form a gel. WLPI also resulted in stronger gels over a range of concentrations compared to BLPI. Nutritional properties of both LPIs were similar, with no significant differences in in vitro protein digestibility (IVPD), and both had very low trypsin inhibitor activity (TIA) and fermentable oligo-, di- and monosaccharides, and polyols (FODMAP) content. The amino acid profiles of both LPIs were also similar, with sulfur-containing amino acids (SAAs) being the limiting amino acid in each case. Environmental impacts revealed by the life cycle assessment (LCA) were almost identical for BLPI and WLPI, and in most categories the LPIs demonstrated considerably better performance per kg protein when compared to cow’s whole milk powder.